Optimizing Flip-Based Islamic Religious Education Learning to Increase Active Participation in Discussions and Self-Expression of Elementary School Students - Rani Hadi Wulandari; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study aims to optimize Islamic Religious Education (IRE) learning through the use of Flip to enhance students’ active participation in discussions and their self-expression at SD Cahaya Cendekia. The background of this research is based on the low level of student engagement in IRE learning, which is still dominated by conventional teaching methods, thus requiring innovative and interactive digital learning media. This study employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with IRE teachers and students, and documentation of learning activities. The findings indicate that the use of Flip as a digital learning medium significantly increases students’ active participation, as reflected in their willingness to express opinions, engagement in discussions, and ability to articulate their understanding of IRE materials through video-based responses. Moreover, Flip fosters a more enjoyable, collaborative, and student-centered learning environment. Therefore, Flip-based IRE learning is effective as an alternative digital learning medium to enhance students’ active participation and self-expression at the elementary school level.